From Content to Commerce: Investigating the Role of Content Marketing in Driving Sales and Brand Engagement - Hadiyati, Rini (Penelitian dan Pengembangan Ilmu, 2024)
This research examines the role of marketing content in driving sales and increasing brand engagement. Through literature analysis and empirical studies, the relationship between marketing content, sales, and brand engagement is explored in depth. The research results show that quality marketing content plays an important role in increasing sales and strengthening brand ties with consumers. In addition, strategies and tactics in implementing marketing content, as well as the challenges and obstacles faced in its use, are also discussed. By taking these findings into account, companies can optimize the use of marketing content to effectively achieve sales and brand engagement goals.